2011
DOI: 10.1002/jgm.1586
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic ultrasound promotes plasmid DNA uptake by clathrin‐mediated endocytosis

Abstract: Background Ultrasound (US) has been widely used to improve the efficiency of nonviral vector transfection. The mechanism of plasmid uptake is usually attributed to sonoporation, although there is not clear evidence for this attribution. Based on our previous results, we hypothesized that other mechanisms, such as endocytosis, could be involved in this process.Methods NIH3T3 cells were transfected with plasmid vector pEGFP-N3 (4.7kb) using a therapeutic US without microbubbles. Bioeffects such as calcium influx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 39 publications
(60 reference statements)
2
36
0
Order By: Relevance
“…As mentioned above, the low frequency ultrasound in the kHz range used in these studies promotes the generation of gas nuclei via rectified diffusion, which can subsequently implode and provoke the same bioeffects as imploding microbubbles. In contrast to these publications, other authors have suggested endocytosis as mechanism when using ultrasound in the absence of microbubbles [101][102][103].…”
Section: Ultrasound Without Microbubblesmentioning
confidence: 88%
“…As mentioned above, the low frequency ultrasound in the kHz range used in these studies promotes the generation of gas nuclei via rectified diffusion, which can subsequently implode and provoke the same bioeffects as imploding microbubbles. In contrast to these publications, other authors have suggested endocytosis as mechanism when using ultrasound in the absence of microbubbles [101][102][103].…”
Section: Ultrasound Without Microbubblesmentioning
confidence: 88%
“…Molecule size was observed to determine decisively which route of uptake occurs, with endocytosis playing a greater role for larger molecules. A few other studies confirmed that endocytosis is indeed involved in ultrasound mediated uptake [15][16][17][18]. In contrast, Schlicher et al [19] blocked endocytic routes and found no difference in uptake of calcein.…”
Section: Introductionmentioning
confidence: 94%
“…Paula et al (2011) reported that the enhanced efficiency of non-viral vector transfection was relative to ROS production using a therapeutic ultrasound. However, the role of ROS in the uptake of PEI/gene particles in cells remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…ROS are increased in a variety of lung diseases (Wood et al, 2010). Enhanced transfection has been related to the extent of ROS production after stress stimuli (Paula et al, 2011); however, the role of ROS in the uptake of PEI/gene particles in cells remains unknown.…”
Section: Introductionmentioning
confidence: 99%